Re-designing the patrimonial public space: Colony Park Pan American Unit and its restoration with an inclusive perspective focused on the elderly in Ciudad Juárez - Moreno Sánchez, Elian Coral (UNIVERSIDAD DE SONORA, 2019)
This essay proposes the potential of the neighborhood park to be experienced and appropriated by its population from a perspective of its social actors, being the case study the park of the Pan American Unit colony in Ciudad Juarez, Chihuahua which has the characteristic of the demographic aging of its residents. Thus and in consecuense the historical trend of this border city was analyzed in terms of open public space related to neighborhood parks and its public policies oriented towards the elderly, currently protagonists of its use, because its number increases significantly and they have a greater availability of time, finally design recommendations are presented for the equipment of the site incorporating the experience and participation of the elderly as well as the theoretical conceptualization regarding the architectural and participatory project workshop of the Universidad Autónoma de Ciudad Juárez that include at the realization of specific proposals to improve the quality of life of the site.